A critical reading of the phenomenon of symbolic violence through the embodiment of the distorted image of women in theater and television drama. - Hussein, Asst.Prof.Dr. Muntaha Tariq Hussein (Sulaimani Journal for Humanities, 2026)
Women's issues are among the most controversial topics in Middle Eastern societies in general. When women's actual presence is affected by what is presented on stage or television, it becomes a matter of great importance and a subject of interest for all circles, especially the academic community. What we see now in some theatrical performances, as well as what we see on television channels in dramas, whether dubbed or locally produced, and in commercials, appears to be a means of communication that presents women and often forces them into all sorts of issues that confuse others and appear as a symbolic, deliberate war on their very being as women in our societies. These portrayals often involve women in various forms of issues that confuse others and appear as a deliberate, symbolic war on their existence as women in our societies. Because the social manifestations of individuals regarding women, their presence, and how they are portrayed in some theatrical productions, coinciding with visual media such as television dramas, are based on a conflict between the cultural sediment present in societal thought and the image of women in ancient culture and heritage built upon male dominance, as well as their portrayal in artistic works, whether in theater or on television, this leads to the creation of a distorted image unrelated to lived reality. This is because it is a product of a culture and heritage saturated across generations and within a structure of prevailing social relations in which no one has a choice. This study attempts, through a systematic academic analysis, to critique the pale image of women presented in both theatrical and television series and to construct an objective approach to the true possibility of women achieving genuine representation and overcoming all obstacles that can perpetuate this distorted image, which is supported by rigid religious thought and outdated social customs.
Keywords: Women; men; violence; blurred image; theater; television